A novel multi-step intercritical heat treatment induces multi-phase microstructure with ultra-low yield ratio and high ductility in advanced high-strength steel. (October 2018) - Xie, Z.J.; Han, G.; Zhou, W.H.; Wang, X.L.; Shang, C.J.; Misra, R.D.K.
Abstract: A significant volume fraction of 26% retained austenite was obtained via a two-step intercritical treatment in a low carbon low alloy steel with ultra-high tensile strength of ~1200 MPa, ultra-low yield ratio of 0.32, excellent uniform elongation of ~16.4% and total elongation of ~23%. The ultra-low yield ratio and excellent uniform elongation implied high work hardening and excellent formability. The high work hardening and ultra-high tensile strength are attributed to deformation-induced twin-martensite. Graphical abstract: Unlabelled Image